2008
DOI: 10.1016/j.jmb.2008.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Dissimilatory Sulfite Reductase from the Hyperthermophilic Archaeon Archaeoglobus fulgidus

Abstract: Conservation of energy based on the reduction of sulfate is of fundamental importance for the biogeochemical sulfur cycle. A key enzyme of this ancient anaerobic process is the dissimilatory sulfite reductase (dSir), which catalyzes the six-electron reduction of sulfite to hydrogen sulfide under participation of a unique magnetically coupled siroheme-[4Fe-4S] center. We determined the crystal structure of the enzyme from the sulfate-reducing archaeon Archaeoglobus fulgidus at 2-A resolution and compared it wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 62 publications
(59 reference statements)
1
101
0
Order By: Relevance
“…To the best of our knowledge, this is the first time a covalent link is observed involving a heme meso carbon and a cysteine residue. The A. fulgidus dSiR, which was purified anaerobically, does not include DsrC (31). We recently obtained crystals from anaerobically purified Dvir, which still showed the presence of the cross-link.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first time a covalent link is observed involving a heme meso carbon and a cysteine residue. The A. fulgidus dSiR, which was purified anaerobically, does not include DsrC (31). We recently obtained crystals from anaerobically purified Dvir, which still showed the presence of the cross-link.…”
Section: Discussionmentioning
confidence: 99%
“…In the A. fulgidus dSiR, the substrate binding site of the DsrA siroheme is also blocked by a tryptophan residue that is sitting right above the iron. In addition, there is an extended loop that blocks access to this heme, which was proposed to have a structural role (31). This loop is absent from Dvir, but in its place, there is an extended loop from the DsrA ferredoxin domain (Gly-257A to Asp-275A) that also shields access to the sirohydrochlorin.…”
Section: The Crystal Structure Of D Vulgaris Dsir Bound To Dsrcmentioning
confidence: 99%
“…Both have similar conformations but are less distorted than the cofactor on the assimilatory sulphite reductase from E. coli. 145 Similarly, non-planar macrocycles have also been implied in nitrite reductases. For example, the structure of oxidized cyt cd 1 (nitrite reductase) from Thiosphaera pantotropha showed a covalently bound, hexacoordinated (HIS, HIS) type c cytochrome and a planar, hexacoordinated (TYR, HIS) heme d 1 .…”
Section: Heme D 1 and Sirohemementioning
confidence: 99%
“…22 To investigate the role of Met175 as the main affinity-regulating residue in the aNiRs, we determined the crystal structures of three Nii3-M175 variants (Nii3-M175G, Nii3-M175E, and Nii3-M175K).…”
Section: Geometries Of the Siroheme And The [4fe-4s] Cluster Of Nii3-wtmentioning
confidence: 99%
“…In this study, we determined the crystal structures of tobacco aNiRs from leaf (Nii3) and root (Nii4). 18 The Nii3 structure was determined to a higher resolution than the previously solved aNiR, assimilatory sulfite reductase (aSiR) and dissimilatory sulfite reductase (dSiR) structures, 15,[19][20][21][22][23][24][25] and therefore precise geometries for the [4Fe-4S] cluster and siroheme could be determined. In addition, based on the detailed structures and on kinetic parameters, comparisons among wild-type Nii3 (Nii3-WT), Nii4-WT, and their variants (Nii3-M175G, Nii3-M175E, Nii3-M175K, Nii3-Q448K, and Nii4-K449Q) showed that the hydrophobicity of the Met175 side-chain was important for the efficient activity of aNiR and revealed that Gln448 of Nii3 and Lys449 of Nii4 play a role in enzyme efficiency (k cat / K m ).…”
Section: Introductionmentioning
confidence: 99%